Stress management a wellness approach - Tummers, Nanette (Human Kinetics, 2013)
Stress is an unavoidable part of our everyday lives--and some of it can be good. But a lot of stress is unhealthy, and most of us don't know how to handle it. Ignoring or mishandling unhealthy stress has all sorts of negative consequences. That's why Stress Management: A Wellness Approach is such a valuable resource. This student-friendly guide identifies stressors in six dimensions of life--physical, emotional, intellectual, social, spiritual, and environmental--and presents tested tools that students can use in managing that stress in healthy ways. This text offers these features: Questions that promote critical and reflective thinking in journal entries and discussions as students look to creatively solve problems; Experiential activities that encourage students to practice stress management techniques. Author Nanette Tummers presents stress management from a holistic viewpoint. She considers not only the symptoms of stress but also the challenges students face in their physical, emotional, intellectual, social, financial, cultural, and spiritual circumstances. Stress Management draws heavily from leading research and best practices from experts in the field of positive psychology, such as Seligman (flourishing), Benson (relaxation response), and Kabat-Zinn (mindfulness). The material cultivates students' strengths rather than pointing out their weaknesses. The book includes sidebars describing resources (books and websites) that instructors and students alike can use in further exploration of issues in stress management. Stress Management helps college students manage stress in today's fast-paced, ever-changing climate: social, culture, politics, economics, technology, and media. It explores key issues of stress and stress management and offers evidence-based research and practical tools that students can use in coping with changes and stress in healthy and positive ways now and throughout their lives.